Synthesis and Characterization of 2-Amino-5-benzoylbenzimidazole Complexes of Manganese(II) and Cobalt(II) - Chandrika Devi, T.; Krishnan, R.; Salahuddin Kunju, A. (Asian Journal of Chemistry, 2016)
Several complexes of 2-amino-5-benzoylbenzimidazole (ABBI) with Mn(II) and Co(II) using different anions, Cl–, Br–, I–, NO3−, CH3COO–, HCOO–, ClO4− and SO42− have been isolated as stable, non-hygroscopic solids and characterized systematic analytical procedures such as cation-anion estimation, elemental analyses, conductivity, magnetic susceptibility and spectral studies have been employed to elucidate the structure with the composition, [M(ABBI)2X2] where M = Co(II) or Mn(II) and X = Cl–, Br–, I–, NO3−, CH3COO–, HCOO–, ClO4− and SO42−. The overall investigations confirm the bidenticity of the ligand, the coordinated nature of the anions and the distorted octahedral geometry of all these complexes studies.